THE MEDIATING ROLE OF WORK DISCIPLINE IN THE RELATIONSHIP BETWEEN EDUCATION LEVEL, COMPETENCY, AND CAREER DEVELOPMENT: EVIDENCE FROM INDONESIAN MARITIME PORT AUTHORITY OFFICERS - Siswanto Siswanto; Sri Rahayu; Rifda Fitrianty (Journal Informatic, Education and Management (JIEM), 2026)
This study examines how education level, competency, and work discipline influence career development among maritime port authority officers, with particular emphasis on the mediating role of work discipline. Drawing upon Human Capital Theory and Competency-Based Management framework, the research addresses a significant gap in understanding how behavioral discipline channels human capital investments into tangible career outcomes within technically specialized bureaucracies. Using a quantitative explanatory design with cross-sectional data collection, the study surveyed all employees at KSOP Class III Tanjung Pakis through structured questionnaires measuring four latent variables. Data were analyzed using Partial Least Squares Structural Equation Modeling with bootstrapping mediation analysis. The findings reveal that all three predictors exert significant positive direct effects on career development, with competency emerging as the dominant predictor followed closely by work discipline. Crucially, work discipline significantly mediates the relationships between both education and competency with career advancement, establishing behavioral reliability as the critical nexus connecting human capital potential to organizational rewards. The substantial explanatory power of the integrated model confirms that merit-based career systems in maritime regulatory agencies must transcend credential accumulation and skill possession to encompass disciplined behavioral expression in high-stakes operational environments. These results inform evidence-based policy formulation for civil service reform initiatives emphasizing performance-oriented human resource management in specialized public sector contexts.